A Versatile Approach for Site‐Specific Lysine Acylation in Proteins. (2nd January 2017) - Wang, Zhipeng A.; Kurra, Yadagiri; Wang, Xin; Zeng, Yu; Lee, Yan‐Jiun; Sharma, Vangmayee; Lin, Hening; Dai, Susie Y.; Liu, Wenshe R.
Abstract: Using amber suppression in coordination with a mutant pyrrolysyl‐tRNA synthetase‐tRNA Pyl pair, azidonorleucine is genetically encoded in E. coli . Its genetic incorporation followed by traceless Staudinger ligation with a phosphinothioester allows the convenient synthesis of a protein with a site‐specifically installed lysine acylation. By simply changing the phosphinothioester identity, any lysine acylation type could be introduced. Using this approach, we demonstrated that both lysine acetylation and lysine succinylation can be installed selectively in ubiquitin and synthesized histone H3 with succinylation at its K4 position (H3K4su). Using an H3K4su‐H4 tetramer as a substrate, we further confirmed that Sirt5 is an active histone desuccinylase. Lysine succinylation is a recently identified post‐translational modification. The reported technique makes it possible to explicate regulatory functions of this modification in proteins.